2006
DOI: 10.1007/11774303_39
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to When Students Game an Intelligent Tutoring System

Abstract: It has been found in recent years that many students who use intelligent tutoring systems game the system, attempting to succeed in the educational environment by exploiting properties of the system rather than by learning the material and trying to use that knowledge to answer correctly. In this paper, we introduce a system which gives a gaming student supplementary exercises focused on exactly the material the student bypassed by gaming, and which also expresses negative emotion to gaming students through an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
0
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 8 publications
5
91
0
12
Order By: Relevance
“…Scooter was designed to reduce the incentive to game the system and to help students learn the material that they were avoiding by gaming, while affecting non-gaming students as minimally as possible. Previous research in the United States found that Scooter reduced gaming, while increasing learning for gaming students (Baker et al 2006); however, these patterns were not statistically significant in the Philippines . The remaining 62 participants (Control or NoScooter group) used a version of the Scatterplot Tutor without the pedagogical agent.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Scooter was designed to reduce the incentive to game the system and to help students learn the material that they were avoiding by gaming, while affecting non-gaming students as minimally as possible. Previous research in the United States found that Scooter reduced gaming, while increasing learning for gaming students (Baker et al 2006); however, these patterns were not statistically significant in the Philippines . The remaining 62 participants (Control or NoScooter group) used a version of the Scatterplot Tutor without the pedagogical agent.…”
Section: Methodsmentioning
confidence: 66%
“…Data were gathered from 126 public high school students in Quezon City, Philippines (labeled PH below), who used a Cognitive Tutor unit on scatterplot generation and interpretation (Baker et al 2006) for 80 min, inside the school's computer center, after school. The students were between 12 and 14 years old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an automated agent that addresses gaming behavior has been developed, based on an automated detector of gaming (Baker et al 2006). This agent gave students supplementary exercises on material bypassed through gaming and displayed displeasure when the student games.…”
Section: The Difference Between Generic Model Parameters and The Inmentioning
confidence: 99%
“…This agent gave students supplementary exercises on material bypassed through gaming and displayed displeasure when the student games. In a classroom study in the USA, this agent reduced gaming by half and improved gaming students' learning relative to the control condition (Baker et al 2006 (2009) found that supportive messages, given when negative affect occurred, improved affect for struggling students, while shake-up messages improved affect for more successful students.…”
Section: The Difference Between Generic Model Parameters and The Inmentioning
confidence: 99%